Post-listing underperformance: Is it really bad to move trading locations? - Cheng, Yingmei (Journal of Corporate Finance, 2005)
We reexamine the post-listing puzzle by studying the stock performance of 2103 firms that moved from NASDAQ to NYSE or AMEX, or from AMEX to NYSE during 1973–1999. The matched four-factor regressions demonstrate that the listing firms do not underperform. Size-and-book-to-market matched factor regression finds that the “post-listing drift” is confined to the small set of firms moving from NASDAQ to AMEX during 1981–1990, within size deciles 3–6 and book-to-market quintiles 1–3. A further control of the industry effect is able to resolve the remaining abnormal returns. Our results are consistent with the pseudo market timing hypothesis in Schultz, (2003) [Schultz, P., 2003. Pseudo market timing and the long-run underperformance of IPOs. J. Fin. 58, 483–517.].